Immunisation schedule of the Pediatric Spanish Association: 2024 recommendations - Francisco José Álvarez García; Antonio Iofrío de Arce; Javier Álvarez Aldeán; Elisa Garrote Llanos; Lucía López Granados; María Luisa Navarro Gómez; Valentín Pineda Solas; Irene Rivero Calle; Jesús Ruiz-Contreras; Ignacio Salamanca de la Cueva; Pepe Serrano Marchuet; Francisco José Álvarez García; et al. (Anales de Pediatría (English Edition))
The AEP 2025 Vaccination and Immunization Schedule recommended for children, adolescents and pregnant women residing in Spain features the following novelties:Due to the increase in measles cases and outbreaks in recent years, we recommend advancing the second dose of measles, mumps and rubella (MMR) vaccine to 2 years of age.As a consequence of the above, since many autonomous communities (ACs) use the quadrivalent vaccine for the second dose of MMR and varicella vaccines, we recommend, for all ACs, advancing the second dose of varicella vaccine to 2 years of age.Due to the very significant increase in cases of pertussis since late 2023 and especially in 2024, we recommend advancing the dose of Tdap given in adolescence to 10–12 years of age.To complete protection against meningococcal disease in adolescence, we recommend vaccination against MenB at age 12 years.We believe that vaccination against seasonal influenza should be routine up to age 18 years, but given the disappointing coverage in children aged 6–59 months, we currently consider that improving this coverage should be prioritised, extending vaccination to children and adolescents aged 5–18 years once this objective has been achieved.Among other aspects, the routine immunization tables for healthy individuals and risk groups, the use of the new extended-valence conjugate vaccines against pneumococcal disease, routine vaccination at 4 months of age with MenACWY and vaccination against SARS-CoV-2 for individuals aged more than 6 months with risk factors remain unchanged with respect to the 2024 schedule. Resumen: El Calendario de Vacunaciones e Inmunizaciones de la AEP 2025 recomendado para niños, adolescentes y embarazadas residentes en España, presenta las siguientes novedades:Debido al aumento de casos y brotes de sarampión en los últimos años, recomendamos adelantar la segunda dosis de triple vírica a los dos años de edad.Como consecuencia de lo anterior, debido a que muchas comunidades autónomas (CC. AA.) usan tetravírica para las segundas dosis de triple vírica y varicela, recomendamos, para todas las CC.AA., adelantar la segunda dosis de vacuna frente a varicela a los dos años.Debido al muy importante aumento de casos de tosferina desde finales del 2023 y especialmente en 2024, recomendamos adelantar la dosis de Tdpa en la adolescencia a los 10-12 años.Para completar la protección frente a los meningococos en la adolescencia, recomendamos la vacunación frente al MenB a los 12 años.Consideramos que la vacunación frente a gripe debe ser sistemática hasta los 18 años, pero dadas las decepcionantes coberturas en los niños entre 6–59 meses, creemos prioritario actualmente aumentar dichas coberturas, y una vez conseguido este objetivo, ampliar la vacunación a niños y adolescentes entre 5–18 años.Se mantienen respecto al calendario 2024, entre otras, las tablas de inmunización sistemática para personas sanas y la de grupos de riesgo, el uso de las nuevas vacunas conjugadas de valencia ampliada frente al neumococo, la vacunación sistemática a los 4 meses de edad con MenACWY, y la vacunación frente al SARS-CoV-2 para personas mayores de 6 meses con factores de riesgo.